The future of Germany - Jaspers, Karl (University of Chicago Press, 1967)
A book by Karl Jaspers needs no introduction by me or by anybody else. However, a few words may not be out of place in this particular case in order to prepare the American reader for the rather astounding fact that a philosopher, and a German philosopher to boot, should have written the politically most improtant book to appear in Germany after the Second World War.